Interplay between Janus Kinase/Signal Transducer and Activator of Transcription Signaling Activated by Type I Interferons and Viral Antagonism - Nan, Yuchen; Wu, Chunyan; Zhang, Yan-Jin (Frontiers in Immunology, 2017)
Interferons (IFNs), which were discovered a half century ago, are a group of secreted proteins that play key roles in innate immunity against viral infection. The major signalling pathway activated by IFNs is the JAK/STAT (Janus kinase/signal transducer and activator of transcription) pathway, which leads to the expression of IFN-stimulated genes (ISGs), including many antiviral effectors. Viruses have evolved various strategies with which to antagonize the JAK/STAT pathway to influence viral virulence and pathogenesis. In recent years, notable progress has been made to better understand the JAK/STAT pathway activated by IFNs and antagonized by viruses. In this review, recent progress in research of the JAK/STAT pathway activated by type I IFNs, non-canonical STAT activation, viral antagonism of the JAK/STAT pathway, relief of the JAK/STAT antagonism for virus attenuation and the potential pathogenesis roles of tyrosine phosphorylation-independent non-canonical STATs activation during virus infection is discussed in detail. We expect that this review will provide new insight into the understanding the complexity of the interplay between JAK/STAT signalling and viral antagonism.